2016
DOI: 10.1682/jrrd.2015.07.0143
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health, caregiver burden, and quality of life in women partners providing care to Veterans with traumatic brain injury

Abstract: Abstract-Families of Veterans with traumatic brain injury (TBI) are often faced with providing long-term informal care to their loved one. However, little is known about how their perceived health and caregiving burden contribute to their quality of life (QOL). The purpose of this descriptive study was to describe perceived health, somatic symptoms, caregiver burden, and perceived QOL and to identify the extent to which these variables are associated with QOL in female partners/ spouses of Veterans with TBI. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 51 publications
5
63
0
Order By: Relevance
“…Our results are in line with the findings from various countries, reported in the meta-synthesis conducted by Dantas et al , showing that parents and families of children with multiple disabilities experience difficulties resulting from the burden of care (health problems, limitations to others activities, increased financial costs) 9. The negative financial impact and the negative planification impact were the most affected dimensions, as previously reported by informal caregivers of patients with other conditions: patients with traumatic brain injury,19 amyotrophic lateral sclerosis,20 cancer21 22 and chronic illness 21. However, considering that caregiver burden may be defined by positive or negative feelings that may be experienced when giving care,23 we also found a substantial positive impact on self-esteem.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results are in line with the findings from various countries, reported in the meta-synthesis conducted by Dantas et al , showing that parents and families of children with multiple disabilities experience difficulties resulting from the burden of care (health problems, limitations to others activities, increased financial costs) 9. The negative financial impact and the negative planification impact were the most affected dimensions, as previously reported by informal caregivers of patients with other conditions: patients with traumatic brain injury,19 amyotrophic lateral sclerosis,20 cancer21 22 and chronic illness 21. However, considering that caregiver burden may be defined by positive or negative feelings that may be experienced when giving care,23 we also found a substantial positive impact on self-esteem.…”
Section: Discussionsupporting
confidence: 79%
“…However, considering that caregiver burden may be defined by positive or negative feelings that may be experienced when giving care,23 we also found a substantial positive impact on self-esteem. This finding was previously reported in other complex conditions: caregivers of blind children,24 traumatic brain injury patients,19 amyotrophic lateral sclerosis patients20 and cancer patients 21 22. It is increasingly recognised that the caregiving experience is not only associated with negative consequences, but can result in subjective gains and satisfaction,25 promote a sense of accomplishment and companionship, and improve self-esteem.…”
Section: Discussionsupporting
confidence: 74%
“…An informal caregiver is a person who offers unpaid or ill-compensated care to a family member, friend, or partner due to illness-related reasons or old age. Results indicate that informal caregivers often experience substantial physical and psychological health consequences as a result of caregiving, such as fatigue [4,5], loss of sleep [6,7], perceived stigma [8,9], anxiety symptoms [10,11], depression disorders [12,13], worsened subjective wellbeing [14,15], and compromised quality of life [16,17]. Evidence further shows that informal caregivers' selfrated health has been in decline for the past ve years, further widening the gap between caregivers and the general population' health status [18].…”
Section: Introductionmentioning
confidence: 99%
“…Saban et al. () reported that caregivers had a high rate of somatic symptoms such as sleep disturbances and fatigue and these, along with caregivers’ perceived burden were predictors of quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sales (2003) reported that providing care could lead to feelings of burden and strain which reduced the perceived quality of life. Saban et al (2016) reported that caregivers had a high rate of somatic symptoms such as sleep disturbances and fatigue and these, along with caregivers' perceived burden were predictors of quality of life. Bischofberger, Jähnke, Rudin, and Stutz (2014) examined the support available for carers in Switzerland for the Swiss Federal Government which subsequently launched a national action plan to help caring relatives.…”
Section: Introductionmentioning
confidence: 99%